Investigation on permeability anisotropy in unconsolidated hydrate-bearing sediments based on pore-scale numerical simulation: Effect of mineral particle shape and pore-filling. (15th March 2023) - Li, Ruirui; Zhang, Luqing; Zhou, Jian; Han, Zhenhua; Pan, Zhejun; Schüttrumpf, Holger
Abstract: Resulting from the preferential alignment of sediment particles, permeability anisotropy of unconsolidated strata is an essential parameter for natural gas hydrate (NGH) exploitation. Fundamentally, the effect of mineral particle shape and pore-filling NGH on the permeability anisotropy are considered in this study. A simulation with combining methods of particle flow code and computational fluid dynamics is conducted to construct a series of numerical samples and calculate the anisotropic permeabilities. Different particles shapes and hydrate saturations are preinstalled in these samples. It is firstly proved that the elongated particles have little effect on permeability anisotropy. Meanwhile, the preferential alignment of plate-shaped particles is the main reason for permeability anisotropy. In principle, the difference between intermediate orthogonal axes and short orthogonal axes of plate-shaped particles makes the tortuosity different in directions, thus inducing the permeability anisotropy. The anisotropy ratio decreases with the increase of hydrate saturation, which is caused by the nonlinear decline of main channel flow resulting from the thrombus-like hydrate particles. The results provide an insight into the formation mechanism of permeability anisotropy and display potential application value in NGH exploitation, groundwater environment protection and geological disaster prevention. Graphical abstract: Image 1 Highlights: Elongated particles have little effect on permeability anisotropy. Difference in intermediate and short orthogonal axes of plate-shaped particles causes permeability anisotropy. Permeability anisotropy ratio decreases with the increase of hydrate saturation.